Unveiling the hidden link: elevated platelets and T cell subsets in 5% of moderate COVID-19 patients 48 days post-onset - An, Hui; Li, Ting; Yang, Lanting; Zhang, Xinyue; Hu, Hao; Zhang, Chen; Wang, Yongyu; Jin, Shengwei; Li, Ming (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionPlatelets are hyperactived during acute COVID-19, promoting clotting and modulating immune-cell responses. Immune thrombocytopenia in adults can manifest as an uncommon complication resulting from various viral infections or as a rare adverse event associated with vaccination. However, their role in convalescent COVID-19 patients remains underexplored. This study examines platelet dynamics early in the pandemic, 48 days post-symptom onset, in unvaccinated patients.MethodsThis longitudinal study included 298 unvaccinated COVID-19 patients (17 mild, 281 moderate) from multiple centers. Clinical evaluations and peripheral lymphocyte subset analyses via flow cytometry were conducted upon admission and on day 48 post-symptom onset (DPSO 48).ResultsAt DPSO 48, 5.3% of moderate COVID-19 patients exhibited high platelet counts (>300×109/L), associated with elevated total T-cells (26.4%), CD4 T-cells (24.4%), CD8 T-cells (36.9%), and Tregs (33.9%) compared to patients with normal platelet counts. However, the CD4/CD8 T-cell ratio and T-cell subset frequencies remained unaffected, indicating ongoing T-cell homeostasis restoration. Additionally, a significant positive correlation (r=0.636, p=0.03) was found between platelet counts and B cells in patients with elevated platelet counts.DiscussionPlatelets may play a pivotal role in immune regulation during the recovery phase of COVID-19. Targeting platelets and their secreted mediators could improve immune balance in patients with immune disorders, highlighting a potential therapeutic approach for enhancing recovery in post-COVID-19 patients.